Color Sensor Application on Electric Drives - Risfendra Risfendra; M Harun Rosyid (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
TCS3200 is one type of sensor that able to identify various types of colors. Its ability to distinguish colors can be used to identify and select various types of objects. To find out the benefits of the TCS300 sensor, a study was made to know implement the TCS3200 sensor function on several electric drive and devices. The TCS3200 sensor application will be made using a 5V DC relay (to start or stop the electric drive) and several electronic devices. This tool uses media in the form of color cards as input data. The card will be read by the TCS3200 sensor, after that the reading data will be received by the Atmega8535 microcontroller, then the results will be displayed on several application devices such as relays, LCD, speaker and LED as outputs. After doing research, the TCS3200 sensor can detect the color cards that have been provided. Based on the program that has been compiled, the Sensor is able to distinguish 9 types of colors, set the switch of 3 electric drive and displaying information of color. TCS3200 adalah salah satu jenis sensor yang mampu mengidentifikasi berbagai jenis warna. Kemampuannya dalam membedakan warna dapat digunakan sebagai pemilih dan pengendali kerja pada beberapa perangkat kelistrikan. Untuk mengetahui manfaat sensor TCS300, sebuah penelitian dilakukan guna mengetahui fungsi sensor TCS3200 pada beberapa penggerak dan perangkat listrik. Pada penelitian ini dibuat sebuah aplikasi sensor TCS3200 dalam bentuk perangkat relay DC 5V (untuk memulai atau menghentikan penggerak listrik) dan beberapa perangkat elektronik. Alat ini menggunakan media dalam bentuk kartu warna sebagai input data. Kartu akan dibaca oleh sensor TCS3200, setelah itu data pembacaan akan diterima oleh mikrokontroler Atmega8535, kemudian hasilnya akan ditampilkan pada beberapa perangkat aplikasi seperti relay, LCD, speaker dan LED sebagai output. Sensor akan bekerja membaca warna dalam jarak 2,5 cm dari objek warna. Setelah melakukan penelitian, sensor TCS3200 dapat mendeteksi kartu warna yang telah disediakan. Berdasarkan program yang telah disusun, Sensor mampu membedakan 9 jenis warna dan membutuhkan waktu 1 - 2 detik untuk mengaktifkan output setelah input warna diberikan.